Critical nursing and health care aide behaviors in care of the nursing home resident dying with dementia - Thompson, Genevieve N. (BMC Nurs, 2019)
BACKGROUND: With the aging of the population, dying with dementia will become one of the most common ways in which older adults will end their final years of life, particularly for those living in a nursing home. Though individuals living with dementia have complex care needs and would benefit from a palliative approach to care, they have traditionally not been recipients of such care. An important aspect of determining quality in end-of-life care is the identification of expert practices, processes or behaviors that may help achieve this care. However, for those living with dementia in nursing homes, we have a limited understanding of how to best support expert end of life care. To redress this gap in knowledge, the purpose of this study was to examine and describe expert care of the individual with dementia approaching death from the perspective of nurses and health care aides (HCAs) identified by their peers as having special expertise in caring for this population. METHODS: A qualitative research design known as Interpretative Description was used to conduct the study. Expert nurses and HCAs were identified through a two-phase nomination process. Individual semi-structured interviews were conducted with consenting participants. Data were analyzed using constant comparative analysis to determine the key critical behaviors. RESULTS: Analysis of data collected from expert nurses (n = 8) and HCAs (n = 7) revealed six critical behaviors when caring for residents dying with dementia. All nurses and HCAs unanimously endorsed that the overarching goal of care is similar for all residents who are actively dying; to achieve comfort. The six critical behaviors in caring for residents dying with dementia included: 1) recognizing and responding to changes in a resident’s pattern of behavior; 2) attending to the person; 3) working with the family; 4) engaging with others; 5) responding after the death has occurred; and 6) having a positive attitude toward care of the dying. CONCLUSIONS: The critical behaviors described by nurses and HCAs in this study provides emerging evidence of best practices in care of those with dementia and their families, particularly near the end of life within the nursing home setting.